(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The main factors effecting the usage of recycled course aggregate (RCA) in concrete mix was its lack of quality. The surface of the recycled aggregate may contain some cement mortar which affects the quality of recycled aggregate. This paper is about to study on recycled aggregate in various test performances by the acid soaking treatment methods using sulphuric acid, nitric acid, hydrochloric acid. FIVE series of concrete mixtures are prepared those are natural aggregate, recycled aggregate, recycled aggregate with HCL, recycled aggregate with H2SO4, recycled aggregate with HNO3. The effectiveness of using these treated recycled aggregate in concrete and strength, durability characteristics of concrete were examined and their properties of aggregates were calculated. In the test results the behaviour of recycled aggregate has improved after soaking in acid treatment. Out of this three acids first recycled aggregates treated with sulphuric acid has given best results, after that nitric acid somehow better but hydrochloric acid has given very poor performance. From the overall study the strength and durability characteristics of concrete by recycled aggregate can be improved in a good way by using the treated recycled aggregate in concrete.